Perancangan Alat Bantu Penghalus Wengku Yang Ergonomis Untuk Meningkatkan Kapasitas Produksi - Mauluddin, Yusuf; Khaerul Anam Siedik, Nizar (Institut Teknologi Garut, 2025)
Wengku is a semi-finished material used in the production of birdcages. The material used to make wengku is bamboo. The process of making wengku is carried out daily. Over time, artisans have been required to produce more than one bundle of wengku per day. Daily demand does not fall below 3 to 4 bundles. Artisans must find ways to increase production capacity to meet this demand. The high demand can negatively impact the artisans' performance due to fatigue and boredom from repetitive work, resulting in suboptimal production. To improve the efficiency of wengku production, a supporting tool is needed to help artisans become more productive. The purpose of this study is to design an ergonomic bamboo-smoothing tool for wengku production that also increases production capacity. The method used is the Ergonomic Function Deployment (EFD) method, which is an evolution of Quality Function Deployment (QFD). EFD creates a new relationship between customer desires and the ergonomic components of a product. The result of this study is the design of an ergonomic bamboo-smoothing tool for wengku, which can increase production capacity. However, the final tool design differs slightly from the initial concept due to adjustments made based on the available raw materials. Testing of the tool showed that it is functional and effective, increasing production capacity by up to two times. Previously, using a manual process, only one bundle of wengku could be produced per day, but with this tool, production can reach up to two bundles per day.